8 - Book Reviews: Kofi D. Benefo and T. Paul Shultz ( 1 994) Determinants of Fertility and Child Mortality in Côte ďlvoire and Ghana (LSMS Working Paper No. 103), The World Bank, Washington, DC, 88pp.: by Babatunde A. Ahonsi - Babatunde A. Ahonsi (Africa Development, 1995)
Abstract